การสังเคราะห์อนุพันธ์ของพอลิฟีนอลจากสารสกัดใบชาเขียวด้วยปฏิกิริยาควบคู่ระหว่างพอลิฟีนอลจากสารสกัดใบชาเขียวกับกรดพาราเมทอกซีซินนามิก - ณัฐพล ตันติเมฆิน (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Polyphenols found in green tea leaves possess a lot of benefits such as antioxidant and anti-inflammatory activities. Here we extracted polyphenol from tea leaves, then coupling them with p-methoxycinnamic acid to form polyphenol para-methoxycinnamate. The coupling product showed broad UV absorption profile with maximum absorption at 310 nm. The coupling product showed antioxidant activity when analysed by DPPH radical scavenging activity. The product also showed good anti-inflammatory activity.